Physical Pretreatments for Improving Nutritive Value of Cyanobacterial Cells - Somrak Rodjaroen (Science Faculty of Chiang Mai University, 2019)
Cell wall is a physical barrier and an unavailable food or feed constituent in industrial applications. Various pretreatment methods (microwave irradiation, ultrasonication, gamma irradiation and electron beam irradiation) were used to improve the nutritive values of cyanobacterial cells. The pretreatment by microwave irradiation at least maintained (lipid, fiber, ash, nitrogen free extract and gross energy) or even improved (protein and neutral detergent fiber) the chemical composition, relative to other tested pretreatments. All pretreatments caused slight changes in the nutritive profile. Microwaving improved also various physicochemical properties in relation to hydrolytic capacity, namely turbidity, microstructure, thermal transition characteristics, and relative crystallinity. These effects contributed to a significant (P < 0.05) overall effect on in vitro carbohydrate digestibility. The findings indicate that microwaving improves the nutritive value and bioavailability of cyanobacteria, with a wide application potential in the pretreatment of food or feed prior to its administration.